Polymer-Derived Si-Based Ceramics: Recent Developments and Perspectives - Aidong Xia; Jie Yin; Xiao Chen; Xuejian Liu; Zhengren Huang (Crystals, 2020)
Polymer derived ceramics (PDCs) are promising candidates for usages as the functionalization of inorganic Si-based materials. Compared with traditional ceramics preparation methods, it is easier to prepare and functionalize ceramics with complex shapes by using the PDCs technique, thereby broadening the application fields of inorganic Si-based ceramics. In this article, we summarized the research progress and the trends of PDCs in recent years, especially most recent three years. Fabrication techniques (traditional preparation, 3D printing, template method, freezing casting techniques, etc.), microstructural tailoring mainly via additive doping, and properties (mechanical, thermal, electrical, as well as dielectric and electromagnetic wave absorption properties) of Si-based PDCs were explicated. Meanwhile, challenges and perspectives for PDCs techniques were proposed as well, with the purpose to enlighten multiple functionalized applications of polymer-derived Si-based ceramics.